Respuesta :

Answer:

x = 6 and y = –5

Step-by-step explanation:

Given equations are –5y + 4x = 49 – – – (1)

                                    7y + 2x = –23  – – – (2)

(1) ⇒ –5y + 4x = 49

         4x = 49 + 5y

           [tex]x=\frac{49+5 y}{4}[/tex]

Substitute [tex]x=\frac{49+5 y}{4}[/tex]  in (2).

[tex]\begin{aligned}&7 y+2\left(\frac{49+5 y}{4}\right)=-23\\&\Rightarrow 7 y+\left(\frac{49+5 y}{2}\right)=-23\end{aligned}[/tex]

⇒ 14y+49+5y= –46

⇒ 19y = –95

y = –5  

Substitute y = –5 in x.

[tex]x=\frac{49+5(-5)}{4}[/tex]

⇒x = [tex]\frac{24}{4}[/tex]

x = 6

Hence, x = 6 and y = –5.

ACCESS MORE